Ameliorative Effect of Alginate Oligosaccharides on NG-nitro-L-arginine methyl ester-Induced Hypertension in Mice - CHEN Junbo, LI Yanxiao, YAN Qiaojuan, JIANG Jun, YANG Shaoqing, JIANG Zhengqiang, (Shipin Kexue)
Objective: To study the ameliorative effect and mechanism of alginate oligosaccharides (AOS) on NG-nitro-L-arginine methyl ester (L-NAME)-induced hypertension in mice. Methods: AOS was used as a preventive treatment for hypertensive mice for 6 weeks. Blood pressure of the mice was monitored, pathological changes in kidney, heart and aortic tissues were observed and the level of oxidative stress was measured. Furthermore, serum levels of total antioxidant capacity (TAC), nitric oxide, angiotensin II, and endothelin-1 were measured, and the protein expression of endothelial nitric oxide synthase (eNOS) in the aorta was also detected. Results: AOS (1.5 g/kg body weight) effectively reduced the systolic blood pressure value of 22.4 mmHg in L-NAME-induced hypertensive mice, and significantly ameliorated pathological changes and oxidative stress injury in the kidney, heart and aorta. Compared with the model group, the serum levels of blood urea nitrogen, creatinine, uric acid, lactate dehydrogenase activity, creatine kinase activity, angiotensin II and endothelin-1 in AOS-treated mice were reduced by 38.0%, 46.5%, 45.2%, 15.9%, 46.4%, 29.5%, and 26.2%, respectively, and serum TAC and nitric oxide concentration were increased by 24.1% and 246.5%, respectively. Furthermore, the protein expression of eNOS in the aorta was significantly increased by 152.9%. Conclusion: AOS has a hypotensive effect in mice, which can inhibit oxidative stress and ameliorate vascular endothelial dysfunction induced by hypertension. This study provides a scientific basis for the potential of AOS as a functional food ingredient for antihypertension.